Soft matters in cell adhesion: rigidity sensing on soft elastic substrates - Schwarz, Ulrich S. (Soft matter, 2007)
This contribution highlights recent advances in our understanding of the relation between soft matter and biological systems. We first discuss the physical scales of living cells which follow from simple scaling arguments developed in soft matter physics. Then we discuss the way cells sense and react to extracellular stiffness as revealed by recent experiments with soft elastic substrates. Theoretical modelling allows addressing of the physical basis of the underlying mechanotransduction processes and its consequences for the organization of single cells and cell communities in soft environments. In the future, these efforts will also lead to an improved understanding of physiological and artificial tissue.